Inhalation of Hydrogen Attenuates Progression of Chronic Heart Failure via Suppression of Oxidative Stress and P53 Related to Apoptosis Pathway in Rats - Chi, Jing; Li, Zizhuo; Hong, Xiaojian; Zhao, Tong; Bie, Yueyue; Zhang, Wen; Yang, Jiaxing; Feng, Ziming; Yu, Zhouqi; Xu, Qiannan; Zhao, Luqi; Liu, Weifan; et al. (Frontiers in Physiology, 2018)
Background: Continuous damage from oxidative stress and apoptosis are the important mechanisms that facilitate chronic heart failure (CHF). Molecular hydrogen (H2) has potentiality in the aspects of anti-oxidation. The objectives of this study were to investigate the possible mechanism of H2 inhalation in delaying the progress of CHF. Methods and Results: A total of 60 Sprague Dawley (SD) rats were randomly divided into four groups: Sham, Sham treated with H2, CHF and CHF treated with H2. Rats from CHF and CHF treated with H2 groups were injected isoprenaline subcutaneously to establish the rat CHF model. One month later, the rat with CHF was identified by the echocardiography. After inhalation of H2, cardiac function was improved vs CHF (p<0.05), whereas oxidative stress damage and apoptosis were significantly attenuated (p<0.05). In this study, the mild oxidative stress was induced in primary cardiomyocytes of rats, and H2 treatments significantly reduced oxidative stress damage and apoptosis in cardiomyocytes (p<0.05 or p<0.01). Finally, as a pivotal transcription factor in reactive oxygen species (ROS)-apoptosis signaling pathway, the expression and phosphorylation of p53 were significantly reduced by H2 treatment in this rat model and H9c2 cells (p<0.05 or p<0.01). Conclusions: As a safe antioxidant, molecular hydrogen mitigates the progression of CHF via inhibiting apoptosis modulated by p53. Therefore, from the translational point of view and speculation, H2 is equipped with potential therapeutic application as a novel antioxidant in protecting CHF in the future.